2019
DOI: 10.1177/0954406219836443
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent PD controller design for active suspension system based on robust model-free control strategy

Abstract: A novel active suspension control design method is proposed for attenuating vibrations caused by road disturbance inputs in vehicle suspension systems. For the control algorithm, we propose an intelligent PD controller structure that effectively rejects online estimated disturbances. The main theoretical techniques used in this paper consist of an ultra-local model which replaces the mathematical model of quarter car system and a new algebraic estimator of unknown information. The measurement of only input and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…In previous works, researchers have been mostly interested in simple quarter car models with two degrees of freedom (Haddar et al, 2019b). In this work, a half car model with four degrees of freedom is presented.…”
Section: Half Car Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous works, researchers have been mostly interested in simple quarter car models with two degrees of freedom (Haddar et al, 2019b). In this work, a half car model with four degrees of freedom is presented.…”
Section: Half Car Modelmentioning
confidence: 99%
“…Several studies were carried to integrate this control method to a quarter car model which is a two degree of freedom vehicle ride model. For example, a novel intelligent--PD controller for the quarter car model was proposed by Haddar et al (2019b). Furthermore, Haddar et al (2017) suggested a method for classical Active Disturbances Rejection Control (ADRC) (Hasbullah et al, 2015) to ameliorate the dynamic response and prevent the problem of uncertainty parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, this proposed strategy requires minimal a priori information of the plant. On the other hand, a new intelligent proportional–derivative (i-PD) controller for active suspension system with 2 degrees of freedom was proposed by Haddar et al 10 In this study, i-PD was designed similarly to active disturbance rejection control (ADRC). For solving the problem of precise tuning process requirement, 11,12 Haddar et al 13 suggested a modification in classical ADRC structure to ameliorate the dynamic response and prevent the problem of sprung mass uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…This article is focused on the data-driven MFAC-based approach. 8,9 Design and analysis of the controller depend only on the physical system’s I/O data, regardless of the order of the system. The controller is a hybrid of SMC and MFAC to control the position of a three-axis camera Gimbal platform.…”
Section: Introductionmentioning
confidence: 99%